2021
DOI: 10.3389/fimmu.2021.695037
|View full text |Cite
|
Sign up to set email alerts
|

Early Elevation of Complement Factor Ba Is a Predictive Biomarker for Transplant-Associated Thrombotic Microangiopathy

Abstract: Transplant-associated thrombotic microangiopathy (TA-TMA) is a fatal complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Previous reports suggest that TA-TMA is caused by complement activation by complement-related genetic variants; however, this needs to be verified, especially in adults. Here, we performed a nested case-control study of allo-HSCT-treated adults at a single center. Fifteen TA-TMA patients and 15 non-TA-TMA patients, matched according to the propensity score, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In the setting of TA-TMA, NETs and soluble C5b-9 have been postulated as potential biomarkers for diagnosis confirmation (100,124), and it might be used to foresee the development of TA-TMA ( 126) and of aGvHD (98). Also, the early assessment of some coagulation factors, such as VWF and TM, together with soluble vascular CAM protein 1 (sVCAM-1), or biomarkers belonging to the complement cascade, such as sC5b-9 or Factor Ba, can predict TA-TMA development (128)(129)(130) and even guide the treatment (131). Jodele et al recently demonstrated that activated terminal complement, measured by elevated blood soluble C5b-9, alone, is a valuable indicator of reduced survival in a prospective study including 130 patients undergoing HCT with a diagnosis of TA-TMA published in 2022 A "dose effect" was observed between higher sC5b-9 levels, higher risk for developing multiorgan dysfunction syndrome, and worse outcomes.…”
Section: Transplant-associated Thrombotic Microangiopathymentioning
confidence: 99%
“…In the setting of TA-TMA, NETs and soluble C5b-9 have been postulated as potential biomarkers for diagnosis confirmation (100,124), and it might be used to foresee the development of TA-TMA ( 126) and of aGvHD (98). Also, the early assessment of some coagulation factors, such as VWF and TM, together with soluble vascular CAM protein 1 (sVCAM-1), or biomarkers belonging to the complement cascade, such as sC5b-9 or Factor Ba, can predict TA-TMA development (128)(129)(130) and even guide the treatment (131). Jodele et al recently demonstrated that activated terminal complement, measured by elevated blood soluble C5b-9, alone, is a valuable indicator of reduced survival in a prospective study including 130 patients undergoing HCT with a diagnosis of TA-TMA published in 2022 A "dose effect" was observed between higher sC5b-9 levels, higher risk for developing multiorgan dysfunction syndrome, and worse outcomes.…”
Section: Transplant-associated Thrombotic Microangiopathymentioning
confidence: 99%
“…The concentration of soluble products derived from complement activation (C5b-9, C3a) may be measured in plasma. It could help in predicting the diagnosis and severity of TA-TMA [164,[172][173][174].…”
Section: Transplant-associated Thrombotic Microangiopathy (Ta-tma)mentioning
confidence: 99%
“…Moreover, an association between sC5b-9 plasma levels and an index of endothelial activation/injury was also reported [ 28 ]. Moreover, Okamura et al found a significant predictive value of early (at 7 days after transplant) high plasma levels of the Ba, a fragment released from complement factor B upon activation of the complement alternative pathway [ 29 ].…”
Section: Complement System Involvementmentioning
confidence: 99%
“…The finding of ADAMTS13 gene variants seems to be consistent with the experimental results obtained by Zheng et al in a mouse model of TMA, which supported a synergistic effect of ADAMTS13 deficiency and complement activation in the pathogenesis of TMA [ 34 ]. However, the importance of complement-related genetic variants in TA-TMA was denied by Okamura et al [ 29 ]. In their nested case-control study of 15 TA-TMA patients and 15 non-TA-TMA patients, no significant differences were identified between the two groups as far as variants in 17 complement system-related genes.…”
Section: Complement System Involvementmentioning
confidence: 99%
See 1 more Smart Citation